Impact sound insulation of floor systems with hollow brick slabs. (December 2020) - Souza, Camila Fernandes Natus; Pacheco, Fernanda; Oliveira, Maria Fernanda; Heissler, Rafael Ferreira; Tutikian, Bernardo Fonseca
Abstract: The improvement of acoustic performance construction systems is crucial. The flaws found during the design of a building are often related to the lack of data that characterize the materials used. Floor slab systems are one of the materials that influence acoustic performance, out of which composite slabs made of ribs and hollow bricks show up as common alternatives. The acoustic performance of this specific material is not entirely known, considering the multitude of coatings that can be added. Therefore, this study compared measurements on impact sound pressure level for one-way rib and hollow brick slabs using multiple coatings and gypsum ceiling, besides the 120 mm thick solid concrete refence slab. The coatings included the use of a concrete cover (50 mm); concrete cover (50 mm) + resilient layer (10 mm) + screed (40 mm); concrete cover (50 mm) + resilient layer (10 mm) + screed (40 mm) + gypsum board ceiling with thickness of 12.5 mm and plenum of 150 mm; concrete cover (50 mm) + screed (40 mm) + the above-mentioned gypsum ceiling; and concrete cover (50 mm) + screed (40 mm). The tests were performed in a vertical acoustic resonant chamber built according to ISO 10140-5:2010. The results showed that the use of gypsum ceiling along with resilient layer under the mortar screed reduced the weighted impact sound pressure level by 41 dB, compared to other samples.